Application of HF Radar in Hazard Management - Mal Heron; Roberto Gomez; Bernd Weber; Anna Dzvonkovskaya; Thomas Helzel; Nicolas Thomas; Lucy Wyatt (International Journal of Antennas and Propagation)
A review is given of the impact that HF radars are having on the management of coastal hazards. Maps of surface currents can be produced every 10–20 minutes which, in real time, improve navigation safety in restricted areas commonly found near ports and harbours. The time sequence of surface current maps enables Lagrangian tracking of small parcels of surface water, which enables hazard mitigation in managing suspended sediments in dredging, in emergency situations where flotsam and other drifting items need to be found, and in pollution control. The surface current measurement capability is used to assist tsunami warnings as shown by the phased-array data from Chile following the Great Tohoku Earthquake in 2011. The newly launched Tsunami Warning Center in Oman includes a network of phased-array HF radars to provide real-time tsunami monitoring. Wind direction maps can be used to locate the position of cold fronts in the open ocean and to monitor the timing and strength of sea-breeze fronts in key locations.